COT-18 Prognosis and problems about secondary intracranial neoplasm in childhood cancer survivors: a single-institution retrospective cohort study. (28th November 2020) - Kagawa, Naoki; Yokota, Chisato; Hirayama, Ryuichi; Kijima, Noriyuki; Nakagawa, Tomoyoshi; Miyamura, Takako; Kinoshita, Manabu; Kishima, Haruhiko
Abstract: Objective: As childhood cancer survivors gradually increased, late complications of treatment have been at issue and risk of secondary neoplasm is increasing cumulatively. We retrospectively analyzed clinical outcome and problems of treatment for secondary intracranial neoplasm. Patients and Methods: 497 patients (children, adolescents and young adults) with malignant central nervous system neoplasm were treated in our institution from 1971 to 2015. 188 cases (37.8%) were enrolled in this follow-up study. Diagnosis of primary neoplasm included low grade glioma (29%), embryonal tumor (23.5%), germ cell tumor (24.5%), ependymoma (8%), other (15%). Results: Fourteen cases of them were diagnosed as secondary intracranial neoplasm. Twelve cases were operated and histopathological diagnosis included 6 glioblastomas, 1 anaplastic astrocytoma, 1 anaplastic ependymoma, 4 meningiomas. In all cases, histopathological finding and molecular profile of secondary intracranial neoplasm differed from that of primary malignant brain tumors. Duration from the first operation of primary tumors to diagnosis of secondary intracranial neoplasm ranged from 5 to 36 years (average: 29.3). In malignant glioma cases except meningioma cases, origin of them was contained in high irradiation field (>40Gy). In malignant glioma cases, Chemotherapies using temozolomide and bevacizumab were selected after tumor removal. In 3 cases of them, reirradiation was performed. Response for treatment was poor or transient in most cases, median survival time was 12 months. Of late complications, such as endocrinological problem needed replacement (55%), cerebrovascular event (15.9%), secondary neoplasm (7.4%), secondary neoplasm was importantly related with prognosis. Conclusion: It is difficult to plan therapeutic strategies against second malignant neoplasm because of lack of information in case of long-term survivors and restriction for first radiation. Clinical outcome of them is poor and new treatment targets should be developed. It is important to plan clinical trials to reduce treatment intensity and usable long-term follow-up system.